2017
DOI: 10.1136/neurintsurg-2017-013433
|View full text |Cite
|
Sign up to set email alerts
|

A new combined parameter predicts re-treatment for coil-embolized aneurysms: a computational fluid dynamics multivariable analysis study

Abstract: PurposeCoil embolization is a minimally invasive method used to treat cerebral aneurysms. Although this endovascular treatment has a high success rate, aneurysmal re-treatment due to recanalization remains a major problem of this method. The purpose of this study was to determine a combined parameter that can be useful for predicting aneurysmal re-treatment due to recanalization.MethodsPatient-specific geometries were used to retrospectively analyze the blood flow for 26 re-treated and 74 non-retreated aneurys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Estimation of recanalization risk has also been attempted using CFD. Fujimura et al 11 performed CFD analysis for 100 coil-embolized aneurysms, including repeat treatments due to recanalization and 74 aneurysms that were not re-treated. They developed a formula called "re-treatment predictor" to predict the risk of aneurysmal re-treatment using logistic regression.…”
Section: Simulation Of Endovascular Devicesmentioning
confidence: 99%
“…Estimation of recanalization risk has also been attempted using CFD. Fujimura et al 11 performed CFD analysis for 100 coil-embolized aneurysms, including repeat treatments due to recanalization and 74 aneurysms that were not re-treated. They developed a formula called "re-treatment predictor" to predict the risk of aneurysmal re-treatment using logistic regression.…”
Section: Simulation Of Endovascular Devicesmentioning
confidence: 99%
“…It was found that the inflow rate on basilar tip aneurysms was a predictor of recurrence after treatment and that changes of the velocity on the neck plane of the aneurysm after treatment were related to aneurysm recurrence . Fujimura et al even proposed a combined parameter combining hemodynamic, morphological, and clinical parameters to predict aneurysm retreatment . In their study the combined parameter more accurately predicted aneurysm retreatment than morphological parameters alone.…”
Section: Resultsmentioning
confidence: 99%
“…When applying the solid model, some studies reconstructed the coil mass using images taken by diagnostic imaging devices, other studies artificially reproduced the state in which the coil mass is deployed by reconstructing the cerebral artery geometries only at locations where there was blood flow or by artificially removing the aneurysm above the aneurysm neck surface from images before coil embolization. [6,8,11,12,16]. Ten reports have adopted this method.…”
Section: • Solid Modelmentioning
confidence: 99%
“…Due to the improvement of computational technology and improvement of image resolution from the development of diagnostic imaging equipment such as computed tomography (CT), magnetic resonance imaging (MRI), and digital subtraction angiography (DSA), an increasing amount of blood flow analysis using computational fluid dynamics (CFD) based on medical images have been performed [3][4][5]. This technique has also been introduced to investigate aneurysm recanalization, and multiple studies have been conducted so far [6][7][8][9][10][11][12]. CFD analysis were conducted on cases where coil embolization were performed, and it has been suggested that recanalization may be predicted by derived hemodynamic factors [8,10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation